Novel direct synthetic route of 2D Prussian Blue analogue, nanocrystalline CuHCF, as highly effective cathode materials for Zn-ion supercapacitors - Maria V. Kaneva; Anastasia K. Bachina; Artem A. Lobinsky (Chimica Techno Acta)
Prussian blue analogues (PBAs) with 2D morphology of nanocrystals have attracted much attention for aqueous electrolyte-based energy storage devices. In this study, we synthesized a 2D Prussian blue analogue, nanocrystals of copper hexacyanoferrate (CuHCF), via a facile stepwise route involving a modified copper substrate of Cu(OH)2 nanorods that was used for the formation of two-dimensional CuHCF crystals. These materials were characterized by powder X-ray diffraction, energy dispersive X-ray microanalysis, X-ray photoelectron spectroscopy and scanning electron microscopy. The cathode based on 2D CuHCF exhibits high specific capacity (240 F/g (63.9 mAh/g) at 0.1 A/g) with excellent cycling stability (98.5% retention after 1000 charge-discharge cycles) in 3 M ZnSO4 electrolyte. The flat two-dimensional morphology of CuHCF provides sufficient ion diffusion channels and the numerous electroactive interfaces for intercalation charge storage.